Resolução de pronomes em posição de sujeito em orações completivas na retoma de antecedentes em SNs complexos: estudo comparativo entre Português Brasileiro e Português Europeu - da Hora, Katharine; Luegi, Paula; Maia, Marcus; Costa, Armanda (Revista da Associação Portuguesa de Linguística, 2019)
In this study we tested, in EP and in BP, complement clauses with a null or an overt pronoun in subject position that is forced by number agreement to retrieve an antecedent within a complex subject NP in the main clause. With an eye-tracking while reading paradigm, we analysed the impact of structural position on pronoun resolution, investigating if the bias described for null-subject and overt-object pronoun resolution for null subject languages replicates for antecedents with different structural positions: null-NP1, the highest structural entity, and overt-NP2, the lowest structural entity. Moreover, we especially investigate the impact of structural position in BP, where c-command relations are considered to be of great relevance for null subject resolution. Results indicate that structural position impacts on pronoun resolution in the predicted way: null-highest NP, overt-lowest NP. Also, BP results reveal that, not only is the null form more constrained by c-command relations, preferentially referring to the c-commanding antecedent (NP1), but also that the overt pronoun does not show a clear bias also when considering structural position (as does not for syntactic function, as shown in previous studies).